Hubungan Sifat-Sifat Fisik Tanah dan Aktivitas Tanah Terhadap Nilai Koefisien Permeabilitas Yang Dipengaruhi Campuran Semen Berdasarkan Uji Laboratorium - Ariana, S. Indira Adhi; Iswan, Iswan; Syah, Aminudin (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Soil is the materials that has a very important role to support the construction on it. Soil permeability value for every construction is different. Such differences affect the strength of a civil construction to be built. The problem that is caused by settlement as seen in Palembapang, Umbul Ligoh, the soil is soft in the rainy season and its bearing capacity becomes low, so it makes a lot of construction problems. Therefore it is necessary to attempt to manipulate the soil permeability value by adding cement as an additive ingredients with the percentage of 0%, 4%, 8% and 12% to a soil permeability values obtained in order to meet the standard of civil construction to be built. Cement has very fine particles so that it can fill the soil pores and has a function as a strong binder. In testing physical properties, the soil includes the classification of A-7-6 soil or poorly categorized soil types.Due to cement addition into soft clay, compaction with the standard proctor experienced a decrease the optimum moisture content (OMC) and an increase in the weight of maximum dry volume, then in the permeability test, the permeability coefficient decreased 2,52%. The composition of the cement mixture affects the value of soil permeability. The lower permeability value follows the amount of cement mixture on the soil. The most change on permeability coefficient was recorded by the sample mixed with 12% of cement.